Agreements and disagreements of modernity in Tegucigalpa, Nineteenth and twentieth century - Navarrete Calix, Daniela (Geografares, 2017)
This article analyzes the urban impact that brought political modernity applied to the city of Tegucigalpa, capital of Honduras. For this we compare diachronically the political-administrative transformation in this urban center: during liberalism of the last quarter of the nineteenth century and early s. XX; and during the neoliberalism of the late twentieth century. The speech of the speakers of liberal and neoliberal modernity will have special attention, as conveys the ideals of governments to achieve progress or development. These yearnings of modernity are reflected in the urban landscape and of course meet and unmeet the aspirations of the citizens of this Central American capital.Keywords: modernity – (neo) liberalism – urban models.